Menertawakan Kejelataan Kita2: Transgresi Batas-Batas Marginalitas dalam Sinetron Komedi Bajaj Bajuri - Irawanto, Budi (Jurnal Ilmu Komunikasi, 2006)
Abstract: Political transition in Indonesia since 1998 has created uncertain situation for most Indonesian people. Moreover, the hard economic condition has multiplied the number of people living below the poverty line. In these circumstances, the light entertainments such as situation comedy, which blends the portrait of ordinary people and their quaint life style, occupied the prime time of television programming in Indonesia. This paper discusses the popularity of the situation comedy Bajaj Bajuri (bajaj literally means âtwo-passenger pedicab motor with scooter machineâ) in contemporary Indonesia. This series is about the daily life of Bajuriâs (bajajâs driver) family and their lower class neighbours in the edge of metropolitan Jakarta (the capital city of Indonesia). Therefore, this paper focuses on the representation of the marginalised people and how television constructed the boundary of marginality. This paper argues that situation comedy is not only reinforcing stereotype of the lower class group but also transgressing the stereotypical image of the lower class by parodying and abusing popular discourse.